2013
DOI: 10.1111/jcpe.12164
|View full text |Cite
|
Sign up to set email alerts
|

Salivary IL‐1β and PGE2 as biomarkers of periodontal status, before and after periodontal treatment

Abstract: The high sensitivity and specificity of salivary IL-1β and PGE2 in identifying periodontitis suggest a potential use as biomarkers for diagnosis of periodontitis presence and severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 20 publications
(21 reference statements)
3
86
1
4
Order By: Relevance
“…36 Yet the variation displayed appears to fluctuate around a homeostatic set point, and several salivary biomarkers have a reliable upper limit that allows for a threshold to be determined that distinguishes health from disease. 35 Using diverse statistical approaches, salivary biomarker concentration thresholds have been reported to provide high sensitivity and specificity for discriminating periodontitis from health, 13,18,29,31,32,37 particularly when unstimulated whole saliva is used rather than stimulated whole or glandular saliva. 15 However, there are few salivary biomarkers that have been studied that reflect the underlying biology of gingivitis in its natural setting.…”
Section: Discussionmentioning
confidence: 99%
“…36 Yet the variation displayed appears to fluctuate around a homeostatic set point, and several salivary biomarkers have a reliable upper limit that allows for a threshold to be determined that distinguishes health from disease. 35 Using diverse statistical approaches, salivary biomarker concentration thresholds have been reported to provide high sensitivity and specificity for discriminating periodontitis from health, 13,18,29,31,32,37 particularly when unstimulated whole saliva is used rather than stimulated whole or glandular saliva. 15 However, there are few salivary biomarkers that have been studied that reflect the underlying biology of gingivitis in its natural setting.…”
Section: Discussionmentioning
confidence: 99%
“…Many characteristics of these cytokines are of interest in orthodontics, since cytokines in the GCF reflect the microenvironment of periodontal tissues, in which orthodontic forces are applied [2,4,15]. Several studies also revealed that cytokines are fundamental in cell signaling in bone [14,18,19] and in mediating mechanically induced bone remodeling (e.g. by orthodontic forces) [1,2,20].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, LD group revealed significant improvement to control PGE 2 levels compared to control group, 1 month and 3 months after periodontal treatment, suggesting that lidocaine subgingival irrigation can modulate inhibitory effect on inflammatory process. Recently, studies have correlated the high levels of PGE 2 in sites with periodontal disease and suggested that PGE 2 can mediate tissue destruction during periodontal disease (Chen et al, 2013;Sánchez et al, 2013). Kumar et al (2013) reported that chronic periodontitis subjects treated by non-surgical periodontal therapy-SRP have mean PGE 2 concentrations in GCF and statistically it reduced significantly after periodontal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…After periodontal treatment, the levels of PGE 2 should be decreased due to re-establishment of healthy periodontal (Sánchez et al, 2013). For several years, studies have been made to improve the outcomes of scaling and root planing using laser application, antibiotic systems, irrigation solutions, chlorhexidine digluconate, povidone-iodine, sodium chloride, etc (Krück et al, 2011).…”
Section: Introductionmentioning
confidence: 99%